2013
DOI: 10.5511/plantbiotechnology.13.0331a
|View full text |Cite
|
Sign up to set email alerts
|

Improving the transformation efficiency of Cucurbita species: factors and strategy for practical application

Abstract: Cucurbita species are refractory to transformation. Hence, the only 2 reports published regarding the transformation of Cucurbita species until our successful transformation of C. moschata (cv. Heiankogiku) in 2011. The efficiency was 2.7±1.3% using wounded explants vortexed with whisker suspension. To improve transformation efficiency, transformation experiments were carried out with various ages of cotyledonary explants. The highest efficiency was obtained with 1-day-old (3.2±0.9%) and 2-day-old (3.3±0.8%) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
(52 reference statements)
2
12
0
Order By: Relevance
“…Previous studies showed that the application of vacuuminfiltration treatment during A. tumefaciens infection significantly improved transformation efficiency in other recalcitrant plants (de Oliveira et al 2009;Bakshi et al 2011). Studies in other plants also showed that the use of filter-paper wicks as a culture support during the co-cultivation step improved transformation efficiency in some plants including recalcitrant crops such as wheat and kabocha squash (Cheng et al 2003;Ozawa 2009;Nanasato et al 2011;Nanasato et al 2013a;Nanasato et al 2013b). Therefore, the combined effect of vacuum infiltration and filter-paper wicks on Jatropha transformation was examined.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies showed that the application of vacuuminfiltration treatment during A. tumefaciens infection significantly improved transformation efficiency in other recalcitrant plants (de Oliveira et al 2009;Bakshi et al 2011). Studies in other plants also showed that the use of filter-paper wicks as a culture support during the co-cultivation step improved transformation efficiency in some plants including recalcitrant crops such as wheat and kabocha squash (Cheng et al 2003;Ozawa 2009;Nanasato et al 2011;Nanasato et al 2013a;Nanasato et al 2013b). Therefore, the combined effect of vacuum infiltration and filter-paper wicks on Jatropha transformation was examined.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, a technique of vacuum infiltration during A. tumefaciens infection has been introduced to improve transformation efficiency of recalcitrant crops including cowpea, citrus, cucumber, and Cucurbita species (de Oliveira et al 2009;Bakshi et al 2011;Nanasato et al 2011;Nanasato et al 2013a;Nanasato et al 2013b). Another technique developed recently involves the use of filter-paper wicks as a culture support during the co-cultivation period, which contributed to the efficient transformation of kabocha squash, rice, and wheat (Cheng et al 2003;Ozawa 2009;Nanasato et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The use of NPTII as a primer because of NPTII is a specific gene not owned by tomato plants (Meissner et al, 1997). In planta transformation has been successfully performed using the floral dip (Ratanasut et al, 2017;Bent 2000;Li et al, 2010;Rod-in et al, 2014;Narusaka et al, 2010;Zang et al, 2006 Clough andBent 1998), by soaking the flower of the plant in the liquid A. tumefaciens culture; the pin pricking (Razzaq et al, 2011;Jaganath et al, 2013;Seol et al, 2008), by pricking the transformation target with the needle smeared with A. tumefaciens; agro-injection (Bratic et al, 2007;Orzaez et al, 2006;Zia et al, 2011), by injecting A. tumefaciens culture directly into the plant tissue or organs; vacuum infiltration (Nanasato et al, 2013;Bratic et al, 2007), by a vacuum to force A. tumefaciens get in into plant cells;…”
Section: Molecular Analysis Of Transformant Candidates Of Tomato Plantsmentioning
confidence: 99%
“…Some improvements in the protocol have been lately reported for melon ( Bezirganoglu et al, 2014 ; Zhang et al, 2014 ), cucumber ( Wang et al, 2015 ), Cucurbita spp. ( Nanasato et al, 2013 ), and watermelon ( Liu et al, 2016 ). In the latter species, an efficient regeneration procedure via SE from embryogenic calli derived from leaf explants has been also recently published ( Vinoth and Ravindhran, 2015 ).…”
Section: Regeneration and Transformationmentioning
confidence: 99%